The longitudinal relationship between loneliness and problematic social networking site use in college students: the mediating role of trait- and state-fear of missing out - Wang, Yuhua; Sun, Yufei; Li, Taiping (Frontiers in Psychology, 2025)
AimsThis longitudinal study explored the mechanisms of loneliness, trait-fear of missing out (trait-FoMO), and state-fear of missing out (state-FoMO) on problematic social networking site use (PSNSU) among Chinese college students.MethodsData were collected in two waves. Overall, 417 college students (45.08% male and 54.92% female, with an average age of 19.87 ± 1.05) completed measures of loneliness and PSNSU at the first time point (T1), and measures of trait-FoMO, state-FoMO, and PSNSU 12 months later (T2).Results(1) There were significant positive correlations among loneliness, trait-FoMO, state-FoMO, and PSNSU; (2) Trait-FoMO and state-FoMO fully mediated the relationship between loneliness and PSNSU; (3) there were two paths of loneliness that influenced PSNSU: loneliness was associated with PSNSU through the mediating role of trait-FoMO alone and the chain mediating role of trait- and state-FoMO.ConclusionThis study highlights the need to accurately distinguish between trait-FoMO and state-FoMO, considering their different underlying mechanisms in addressing problematic network problems among college students.